Pemanfaatan Daun Kelor Dan Bonggol Pisang Sebagai Pupuk Organik Cair Untuk Pertumbuhan Tanaman Bayam (Amaranthus Sp.) - Cahyono, Ragil Nur, Dra. Aminah Asngad, M.Si (2016)
Utilization of Moringa leaves and banana weevil as a liquid organic fertilizer had not previously been done. Moringa leaves and banana weevil could be combined as the manufactured of liquid organic fertilizer and optimal cost for the plant. The content of Moringa leaves and banana weevil would stimulate more optimal for plant growth. The purpose of this study was to determine the concentration and interval combination of liquid organic fertilizer used Moringa leaves and banana weevil best for the growth of spinach plants. This study used an experimental method with two factors, one was the concentration of fertilizer (P1 = 40%, P2 = 50%, and P3 = 60%) and factor 2 interval watered liquid fertilizer (I1 = 3 days, I2 = 4 days and I3 = 5 days) with 9 treatments and two replications. The parameters observed were plant height, number of leaves, and the fresh weight. Observations were made every two weeks for one month. Datas were analyzed with ANOVA two lanestreatment. The results showed that the combination of the best treatments for high growth of stems was on P3I1, while the combination of the best treatment for the growth number of leaves and fresh weight was on P3I2. There was an interaction effect between the concentration of fertilizer and watered intervals on the growth of stem height. However, the growth number of heavy fresh leaves and does'nt interaction effect between these two factors.